Critical ethnography in maternity care research: bridging creativity and rigour – a discussion paper. (August 2021) - Newnham, Elizabeth; Small, Kirsten; Allen, Jyai
Highlights: Ethnographies of healthcare services can reveal actions, beyond intent or lip-service to professional philosophy In maternity care, critical ethnography can make visible the power that limits women's choices and midwifery practice There is scant literature specific to maternity care to guide the conduct of ethnographic research We discuss our critical ethnographic research and how attention to rigour can help maintain the creativity of ethnographic research Abstract: Ethnography is a useful research method for maternity care research, because it can identify elements of actual practice that may be missed using non-observational research. However, because of the relative creative freedom of writing ethnography, it can be difficult for novice researchers, because there is no particular set of steps to follow. Much of the work of an ethnography is actually just watching, thinking and writing. In this paper we discuss our three individual doctoral research projects— all variations of critical ethnography—in order to present some of the creative variety of ethnography in maternity care research and to promote discussion within this field about how to maintain robust ethnographic research while keeping hold of its creative aspects. Attempts to standardise ethnographic research have the potential to curtail a very flexible methodology and constrain the knowledge generating work of the researcher. We encourage fellow maternity researchers to contribute to literature on ethnographic methodology in order to expand and refine use of this methodology in maternity care settings.